Implementation of PP No.19 of 2005 concerning National Education Standards : Case Study of the Implementation of School-Based Management at SMK Muhammadiyah 1 Taman Sidoarjo - Dwi Oktavianto, Vicky (ann4publisher@gmail.com, 2023)
This study aimed to ascertain the degree of autonomy possessed by SMK Muhammadiyah 1 Taman Sidoarjo as well as the degree of stakeholder participation, cooperation, and accountability on the side of the institution. Descriptive analysis, or the analysis of data by summarizing or characterizing the data obtained as they are without drawing broad inferences or generalizations, was the method of data analysis employed in this study. The following points are discussed about the implementation of school-based management (SBM): 1) School independence is demonstrated by the authority of the school to develop curricula and learning programs following the initiative of school members and in compliance with applicable laws and regulations; and 2) Internal school cooperation has been well established with synergies between school activity units, whether they are school teamwork or individual residents schools. The government, the local school committee's community, and business and industry have all benefited from school collaboration with the outside world. 3) Contribution to the implementation of educational initiatives through monetary and financial support, material and facility support, intellectual support, and support funds. 4) It is remarkable that the school is transparent about its funding and programs. School staff workers and committees collaborate to create school programming and budgets. 5) The school has provided citizens, school committees, foundations, and the government with accountability for the procedures and outcomes of program execution and school finances, which falls under good school accountability.